Digital Fashion Technologies & Practices: Design Driven Sustainable Transition in Fashion Industry - Ludovica Rosato; Alberto Calleo (DIID, 2024)
Contemporary clothing manufacturing, purchasing and consumption models have made the fashion industry the second most polluting industrial sector. This contribution aims at analysing promising technologies, methodologies and practices that are tackling environmental sustainability issues related to the fast-fashion industry. The contribution analyses how, leveraging on technology innovation, the combination of tangible processes, such as the selection of production means and materials, and intangible practices, such as digital fashion, designers can contribute to the sustainable transition of the fast-fashion sector mediating between customer expectations, production economy constrains and environmental sustainability.